2011
DOI: 10.18553/jmcp.2011.17.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Cost Savings Associated with the Transfer of Office-Administered Specialty Pharmaceuticals to a Specialty Pharmacy Provider in a Medical Injectable Drug Program

Abstract: C O N T E M P O R A R Y S U B J E C T• This MCO's solution to the clinical, financial, and operational challenges of managing office-administered specialty pharmaceuticals involved (a) the transfer of certain office-administered, nononcology medical injectable drugs (MIDs) from "buy and bill" physician reimbursement using HCPCS (J) codes to purchase from a single, exclusive SPP at discounted reimbursement rates based on National Drug Code (NDC) numbers, and (b) reduction in physician reimbursement for MIDs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…19,20 In particular, studies have found that medication counseling and reconciliation may reduce 30-day readmission rates. 14,21,22 Pharmacists are increasing their role in patient care interventions, [23][24][25][26][27] including care transition programs, 15,19,21 but more research is needed to assess the impact of such programs.…”
mentioning
confidence: 99%
“…19,20 In particular, studies have found that medication counseling and reconciliation may reduce 30-day readmission rates. 14,21,22 Pharmacists are increasing their role in patient care interventions, [23][24][25][26][27] including care transition programs, 15,19,21 but more research is needed to assess the impact of such programs.…”
mentioning
confidence: 99%
“…As shown in Figure 2, specific specialty management programs and policies include the following: (a) channel management that may result in narrowing the specialty drug pharmacy provider network to a limited number of dispensing pharmacies in order to obtain greater unit cost discounts; (b) contracting and rebates that may result in pharmaceutical manufacturer inflationary price protection and rebate optimization via formulary preferred product(s) steerage; (c) implementing utilization management or medical policy pre-authorization to prevent unsafe use or investigational use including requirements to try the preferred formulary product(s) prior to the nonpreferred product(s); and (d) coordination of care between the medical and pharmacy benefit clinical care teams, for example, disease management and specialty pharmacy care management. 7,[16][17][18][19] The goals of these programs include helping members understand and manage their conditions; providing guidance in using health care resources judiciously; maintaining or improving adherence to the member's care plan, including specialty drug therapy; and obtaining best pricing.…”
Section: Prevalence Treatment Rates and Costs By Chronic Conditionmentioning
confidence: 99%
“…Specialty management strategies include custom formularies and benefit designs, clinical utilization management, provider reimbursement contracts, fraud and billing error monitoring, and distribution channel management. [13][14][15] Formulary management of specialty products has been used by payers for many years, 16 and nearly 10% of the cost of self-administered specialty products can be avoided with a robust formulary optimization program. However, most of the distribution-related specialty savings for self-administered drugs have been extracted due to pervasive specialty pharmacy distribution contracting.…”
Section: Opportunities and Challenges Of Specialty Pharmaceuticalsmentioning
confidence: 99%